Coercive Properties of Magnetic Garnet Films - Gábor Vértesy (Crystals, 2023)
Magnetic garnet films represent a wide family of materials. By the proper choice of chemical composition and growth parameters, their magnetic behavior can be tuned in a very wide range. On one side, they are suitable for many different applications; on the other side, they are optimal model materials for studying the basic magnetization processes. Many assumptions of the existing theories can be checked or validated by magnetic garnet film investigation. Their production technology was developed many decades ago, but even nowadays, magnetic garnet films have been intensively studied, and newer and newer application possibilities have been found. In this review paper, those results are summarized, which are connected with their coercive properties. Coercivity, or coercive force, is a frequently used magnetic characteristic, but usually, it is considered rather a technical parameter. It is shown that there is no correlation between the so-called “technical coercive force” (which is the half-width of a major hysteresis loop) and the domain wall coercivity (this is frequently called a domain wall pinning field). This latter parameter is considered a real characteristic of domain wall movement. If magnetic garnet films are investigated, the correlation between moving domain wall and material defect structure can be studied. In this paper, the very complex feature of coercivity is shown. It is demonstrated that the domain structure, the properties of domain walls, the existence of mechanical stresses, the temperature, the size of the sample and many other parameters have an influence on the measured coercivity.